Bibliometric Mapping of Green Economy in Development - Darmawansyah, Trisna Taufik; Aguspriyan, Yani; Masykuroh, Nihayatul; Sudirja, Dede; Setiadi, Rezki Metha; Surahman, Surahman; Aini, Asti (Faculty of Social Science, Universitas Negeri Padang, 2024)
This research presents a bibliometric analysis of the term